PALYNOMORPHOLOGICAL STUDIES ON FAMILY MIMOSACEAE - AJAY V. RAJURKAR; JAYKIRAN A. TIDKE; SAGAR S. JADHAV (International Journal of Pharma and Bio Sciences, 2013)
Pollen morphology of eight genera belonging to sub-family Mimosaceae of Leguminosae have been examined by Light and Scanning Electron Microscope (SEM). The Sub-family Mimosaceae is referred to as eurypalynous family because of the great variety of pollen types found in its members. Pollen morphological characters are found to be significantly helpful at generic or species level. The morphological variation in size, shape, surface structure and surface pattern occurs in all studied acetolysed and unacetolysed pollen grains. The present reports gives an account of pollen morphological variations in eight genera of Mimosaceae growing in Amravati University campus.